Beam identification in multiple-beam echo sounders - Tucker, M. J. (The International Hydrographic Review, 2025)
This manuscript is a reprint of the original paper previously published in 1961 in The International Hydrographic Review (IHR, https://ihr.iho.int/): Tucker, M. J. (1961). Beam identification in multiple-beam echo sounders. The International Hydrographic Review, 38(2), 25–32. https://journals.lib.unb.ca/index.php/ihr/article/view/26493